Iatrogenic third-degree burn caused by off-label use of an infrared radiant heat lamp in a patient with accidental hypothermia - Kosuke Ishikawa; Taku Maeda; Toshihiko Hayashi; Ryuji Shichinohe; Naoki Murao; Masahiro Hojo; Riri Ito; Masayuki Osawa; Yuhei Yamamoto; Emi Funayama (Elsevier, 2021)
We report a case of third-degree burn involving 5% of the total body surface area caused by off-label use of Hanautherm®, an infrared radiant heat lamp for bed-warming, in a patient with severe accidental hypothermia. This iatrogenic burn required repeated surgical interventions and long-term hospitalization and caused subsequent cosmetic disfigurement and functional disability. To our knowledge, this is the first reported adult case of iatrogenic burn occurring during treatment for hypothermia. Radiant heat lamps should never be used for rewarming of patients with hypothermia without careful observation.